Contraception in Medically Complex Adolescents and Young Adults - Addison J; Hassan A; DiVasta A (Dove Medical Press, 2024)
Jessica Addison,1,2,* Areej Hassan,1,2,* Amy DiVasta1,2 1Division of Adolescent/Young Adult Medicine, Boston Children's Hospital, Boston, MA, USA; 2Department of Pediatrics, Harvard Medical School, Boston, MA, USA*These authors contributed equally to this workCorrespondence: Jessica Addison, Division of Adolescent/Young Medicine, Boston Children's Hospital, LO-306, 300 Longwood Ave, Boston, MA, 02115, USA, Tel +1 202-549-4001, Email jessica.addison@childrens.harvard.eduAbstract: Contraception is a significant part of comprehensive sexual and reproductive health (SRH) care for adolescents and young adults (AYA). While providers may assume that AYA with chronic illness are not sexually active, studies have shown that there are no differences in their sexual practices compared to their counterparts without an illness. This assumption may result in less SRH screening, preventative services, and counseling by providers resulting in decreased basic sexual knowledge, increased risk of unplanned pregnancy, and other health disparities. Sexually active AYA with medical complexity are particularly in need of contraception for a variety of reasons. A better understanding of the complexities around contraception counseling can help increase utilization rates, improve shared-decision making around family planning, and reduce the stigma around sexual health counseling in this population. We have included three sections. First, a general overview of contraception methods. Next, an overview of contraceptive methods currently available, their efficacy, and medical eligibility criteria for their use in AYA who have certain characteristics or medical conditions. Finally, cases adapted from real clinical scenarios to highlight specific recommendations for contraception in AYA women living HIV, autoimmune conditions, and those who have received a solid organ transplant. This information will help providers to consider the multiple factors that influence contraception decision-making (including clinical status, thrombosis risk, medication interactions, safety), and optimize care for AYA living with chronic illness.Keywords: adolescent, young adult, contraception, sexual health, chronic illness